Improving Academic Self-Concept and STEM Identity Through a Research Immersion: Pathways to STEM Summer Program - Betz, Amy R.; King, Brenee; Grauer, Bette; Montelone, Beth; Wiley, Zelia; Thurston, Linda (Frontiers in Education, 2021)
Undergraduate research opportunities have been demonstrated to promote recruitment, retention, and inclusion of students from underrepresented groups in STEM disciplines. The opportunity to engage in hands-on, discovery-based activities as part of a community helps students develop a strong self-identity in STEM and strengthens their self-efficacy in what can otherwise be daunting fields. Kansas State University has developed an array of undergraduate research opportunities, both in the academic year and summer, and has established a management infrastructure around these programs. The Graduate School, which hosts its own Summer Undergraduate Research Opportunity Program aimed at URM and first-generation college students, coordinates the leadership of the other grant-funded programs, and conducts a series of enrichment and networking activities for students from all the programs. These include professional development as well as primarily social sessions. The Kansas LSAMP, led by Kansas State University, created a summer program aimed at under-represented minority community college students enrolled in STEM fields to recruit them into research opportunities at K-State. There has been strong interest in the program, which incorporated university experience elements in addition to an introduction to STEM research and the four-year university. In the 5 years since the program’s inception, cohorts of nine to fourteen students came to K-State each year for eight-week experiences and took part in both cohort-based sessions and individual mentored research experiences. The two-fold focus of this program, Research Immersion: Pathways to STEM, has resulted in the majority of the students presenting a poster at a national conference and transferring to a STEM major at a four-year institution. Survey results showed that the program was successful at improving STEM identity and academic self-concepts. Qualitative feedback suggested that the two parts of the program worked together to increase interest and self confidence in STEM majors but also ensured that students connect with other students and felt comfortable in the transition to a 4-year institution.